Pharmacological correction of obesity-induced autophagy arrest using calcium channel blockers - Park, Hwan-Woo (2014)
Autophagy deregulation during obesity contributes to the pathogenesis of diverse metabolic disorders. However, without understanding the molecular mechanism of obesity interference in autophagy, development of therapeutic strategies for correcting such defects in obese individuals is challenging. Here we show that chronic increase of cytosolic calcium concentration in hepatocytes upon obesity and lipotoxicity attenuates autophagic flux by preventing the fusion between autophagosomes and lysosomes. As a pharmacological approach to restore cytosolic calcium homeostasis in vivo, we administered the clinically approved calcium channel blocker verapamil to obese mice. Such treatment successfully increases autophagosome-lysosome fusion in liver, preventing accumulation of protein inclusions and lipid droplets and suppressing inflammation and insulin resistance. As calcium channel blockers have been safely used in clinics for the treatment of hypertension for more than thirty years, our results suggest they may be a safe therapeutic option for restoring autophagic flux and treating metabolic pathologies in obese patients.